The Abbott Pandemic Defense Coalition: a unique multisector approach adds to global pandemic preparedness efforts - Averhoff, Francisco; Berg, Michael; Rodgers, Mary; Osmanov, Saladin; Luo, Xinxin; Anderson, Mark; Meyer, Todd; Landay, Alan; Gamkrelidze, Amiran; Kallas, Esper G.; Ciuoderis, Karl; Hernandez, Juan Pablo; et al. (International journal of infectious diseases, 2022)
•Enhanced capacity for the detection of pandemic threats is needed globally.•Abbott launched the Abbott Pandemic Defense Coalition (APDC) in early 2021.•The APDC aims for the early detection of infectious disease threats of pandemic potential.•APDC has the novel capacity to rapidly develop and deploy diagnostics targeting new pathogens. Detection and epidemiologic characterization of infectious disease outbreaks are key for early identification and response to potential pandemic threats. The rapid global spread of severe SARS-CoV-2 in 2020 highlighted the critical role of diagnostics in understanding the epidemiology of the virus early in the pandemic. As a natural extension of Abbott's work in diagnostics, virus discovery, and virus surveillance, the Abbott Pandemic Defense Coalition (APDC) was launched in early 2021. The APDC is a global multisector scientific and public health partnership whose primary objective is the early detection and mitigation of infectious disease threats of pandemic potential. As of January 2022, the APDC network has partners on 5 continents including academic institutions, governmental, and nongovernmental organizations. A novel element of the APDC is the capacity for early development and rapid deployment of scalable, quality diagnostics targeting newly identified pathogens of pandemic potential.